The Effectiveness of the 'One Student One Breastfeeding Woman' Program on Breastfeeding Success - Lisa, Ulfa Farrah; Wijayanti, Feri Anita (Women, Midwives and Midwifery, 2025)
Background: Breastfeeding success plays a crucial role in optimizing child growth and development. Maternal knowledge, satisfaction, and self-efficacy are key influencing factors, all of which can be enhanced through support from health professionals in the form of guidance and counseling during the breastfeeding period. In Indonesia’s Midwifery Professional Education curriculum, one of the learning outcomes for students is providing care for breastfeeding mothers. Purpose: This study aimed to determine the effectiveness of the One Student One Breastfeeding Woman program on breastfeeding success. Methods: This was a quasi-experimental study using a pre-post design without a control group. The study involved 23 breastfeeding mothers in Padang City who participated in the One Student One Breastfeeding Woman program. Data collection employed three instruments: the Maternal Breastfeeding Evaluation Scale (MBES) to measure satisfaction, the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) to measure self-efficacy, and a breastfeeding knowledge questionnaire developed by Susiloretni et al. The study received ethical approval. Data were analyzed using paired t-tests with a 95% confidence interval. Results: The findings showed significant improvements across all variables. The mean knowledge score increased from 20.7391 (SD = 2.32022) before the intervention to 23.3043 (SD = 1.94082) after (p < 0.001). Maternal satisfaction improved from 62.4348 (SD = 9.42832) to 67.6522 (SD = 7.14530) (p = 0.049). Self-efficacy increased from 38.9565 (SD = 10.85641) to 45.6087 (SD = 8.02688) (p = 0.036). Conclusion: The One Student One Breastfeeding Woman program was found to be significantly effective in improving breastfeeding success by enhancing maternal knowledge, satisfaction, and self-efficacy. This program can bze integrated as part of the learning outcomes in postpartum and breastfeeding care within the Midwifery Professional Education curriculum and may serve as a strategy to support exclusive breastfeeding achievement. This finding highlights the potential of student-led breastfeeding support as an innovative model for maternal and child health promotion.